A Case Report of Female Systemic Lupus Erythematosus and Cerebral Lupus as The Complication : Diagnosis and Treatment - Stefani Irene Darmanto; Sherina Ayu Pitaloka; Silvia Reynata Fauzia; Sonia Kartika Ayu; Soraya Nur Fajrina; Hendrata Erry Andisari; I Wayan Suryajaya (RSUP Dr. Kariadi, 2024)
BACKGROUND : Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that affects multiple systems in the body. Because clinical manifestations can appear in different organs, the complications are diverse and can be quite severe, one of which is cerebral lupus or neuropsychiatric systemic lupus erythematosus (NPSLE). It includes neurological and psychiatric syndromes in SLE patients where other causes have been ruled out. We reported a case of SLE manifestation with cerebral complication involvement. AIMS : This case report aims to provide insights and expect to offer an understanding into the clinical presentation, diagnosis, and management of a patient with cerebral lupus. CASE PRESENTATION : 18-year-old Indonesian woman with complaint of sudden seizure was referred to the Emergency Unit of Dr. Ramelan Naval Central Hospital Surabaya. She had previously been diagnosed with SLE back in 2022 and consistently does a monthly checkup in the internal medicine clinic at Dr. Ramelan Naval Central Hospital Surabaya. Initial examinations revealed signs of infection, slight electrolyte imbalances, and a flare phase of SLE, but no abnormalities in imaging tests. She received initial treatments of loading phenytoin along with mecobalamin injection, vitamin B6, methamizole, and cefobactam. Over the course of her hospital stay, with no further seizures, she was discharged with medication for continued treatment and a scheduled follow-up. CONCLUSION : This case of cerebral lupus is rare. SLE can damage the blood brain barrier (BBB), causing neuropsychiatric complications.